A dynamic geo-based resource selection algorithm for LTE-V2V communications - Xinyu Gu; Yi Ding (EURASIP Journal on Wireless Communications and Networking, 2018)
Abstract The geography-based (geo-based) resource selection algorithm is one of the feasibility schemes of third-generation partnership project (3GPP). However, most researches about it ignore the impacts of boundary interference and vehicle density. Therefore, this paper firstly puts forward an enhanced geo-based resource selection algorithm (EGRSA). This algorithm can eliminate the boundary interference through randomizing subframes of each sub resource pool. On the basis of EGRSA, the dynamic geo-based resource selection algorithm (DGRSA) is proposed to guarantee the reliability of communication when vehicle density is nonuniform. In DGRSA, mapping relationships are changed dynamically by grouping and optimal matching, and the size of each sub resource pool can also be adjusted. The system level simulation results indicate that the EGRSA is able to improve the packet reception ratio (PRR) and reduce the number of boundary collisions. Meanwhile, the proposed DGRSA further promotes the PRR when vehicle density is in a non-uniformity distribution because of traffic jam.